Makna Perbandingan Ketidakadilan Gender Dalam Film Vina dan Film Munkar Karya Anggy Umbara - Faddillah, Azura; Nasution, Nurhasanah (Universitas Muhammadiyah Sumatera Utara, 2024)
Gender inequality is a complex and widespread issue that is consumed by modern society. The struggle to achieve gender equality has become a focus in the field of mass media. Gender is considered an attribute that is used as a basis for identifying differences between men and women from a social perspective, especially in the field of mass media. Film as a medium has a significant influence in shaping people's views about this content. One of the films that represents gender inequality is the film Vina and the film Munkar. Researchers analyze the comparative meaning of gender inequality in the films Vina and Mukar by Anggy Umbara. This research uses a qualitative descriptive method. The theory used in this research is Charles Sanders Peirce's semiotic theory which analyzes three stages of meaning, namely sign, object and interpretant. The data collection techniques used are observation and documentation related to feminism by observing, recording and analyzing indicators of feminist issues in scenes, dialogue and gestures. The data analysis technique uses Charles Sanders Peirce's semiotic approach which emphasizes solving meaning in three main elements, namely sign, object and interpretant. The research results reveal that both films depict a deep perspective on how marginalization, subordination, physical violence, gender stereotypes and cultural values influence women's lives in the importance of gender awareness to achieve fairer equality